An Explanation for Internet Use Obstacles Concerning E-Learning in Iran - Rabiee, Ali; Nazarian, Zahra; Gharibshaeyan, Raziyeh (International Review of Research in Open and Distributed Learning, 2013)
E-learning is advancing in Iran right now. The Iranian higher education system is applying electronic learning in order to conquer the limitations of the existing education system. These limitations include the growing number of applicants for entering universities, lack of classrooms for education, and universities’ tensions in replying to these needs. Also, ease of access to e-learning and a lack of financial resources are reasons for applying e-learning in Iran. In addition, the Iranian higher education system wants to progress with global changes in the information era and they see it as necessary to acquire information and knowledge. Meanwhile, web technology enjoys a special and significant role. This paper investigated barriers to using internet technology for e-learning in the Iranian context. The methodology employed both qualitative and quantitative techniques. In the qualitative stage, exploratory observations of eight virtual institutes for higher education and interviews with 20 experts in these institutes were used. The analysis of the data showed that socio-cultural, structural, educational, economic, and legal factors were the most prominent obstacles to web technology use; each factor comprised a number of components. So as to check the primacy of the factors and the extracted components at large, the researchers developed a Likert-type questionnaire; the questionnaire, which comprised the five types of obstacles and their related components, enjoyed a high degree of validity and reliability. Twenty students in each of the eight institutes were asked to fill out the questionnaire. The analysis of the data showed that socio-cultural factors are the most influential barriers to use of the Internet in e-learning.